Information model in an Open Archival Information System (OAIS) for Bahagian Arkib & Muzium (BAM) UiTM / Zul Azfar Sulaeman - Sulaeman, Zul Azfar (2011)
This report describes a project carried live on the Bahagian Arkib UiTM using metadata and standardization. The function of OAIS Information Model is to help provide information and metadata about archive easily to see, either manually or electronically as a reference to management, researchers and future generations. Bahagian Arkib UiTM information model, need to be describe about its metadata using standard that already being used in National Archive data description. General International Standard Archival Description (ISAD(G)) and Open Archival Information System (OAIS) Information Model are being used to standardize between Bahagian Arkib UiTM and National Archive of Malaysia. The importance of standardization between these two companies is to make information shareable because these two companies share their information together